Paradigma and Programs Multicultural Education in Inclusive Madrasah - Ahmad Dwi Nur Khalim; Wensislaut Parut (Journal of Contemporary Islamic Education, 2025)
Multicultural education in inclusive madrasah plays a crucial role in fostering collective awareness of diversity, particularly in Indonesia, a nation renowned for its cultural, ethnic, and religious plurality. Amid the complexities of globalization, inclusive madrasahs hold a strategic position in creating a learning environment that values differences. This study aims to analyze the implementation of multicultural education at MTs Negeri 6 Sleman, which operates as an inclusive madrasah, with a focus on the integration of multicultural values into its curriculum and learning processes. The research employs a qualitative approach using a case study method, with MTs Negeri 6 Sleman as the primary site of investigation. Data collection was conducted through semi-structured interviews, observations, and documentation. The collected data were analyzed using an interactive analysis model, encompassing data reduction, data presentation, and conclusion drawing. The findings reveal that the multicultural education paradigm at MTs Negeri 6 Sleman is rooted in a commitment to creating an inclusive environment that respects cultural, religious, and social diversity. This paradigm is actualized through the integration of multicultural values within the curriculum and teaching approaches that instill empathy, tolerance, and equity. Furthermore, MTs Negeri 6 Sleman successfully incorporates the five dimensions of multicultural education proposed by James A. Banks: content integration, the knowledge construction process, prejudice reduction, equity pedagogy, and the empowerment of school culture. The inclusive curriculum at MTs Negeri 6 Sleman facilitates positive interactions among students and between students and teachers, contributing to a harmonious and inclusive educational atmosphere.